2018
DOI: 10.3389/fmicb.2018.00724
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and Antibiofilm Activities of Psychorubrin, a Pyranonaphthoquinone Isolated From Mitracarpus frigidus (Rubiaceae)

Abstract: Psychorubrin, a natural pyranonaphthoquinone found in different plants, has become an interesting compound in the search for new antimicrobial therapeutic agents. Here, we investigated the potential antagonistic activity of psychorubrin against planktonic and biofilm bacteria. First, psychorubrin was tested against several Gram-positive and Gram-negative bacteria strains by a broth microdilution susceptibility method. Second, bacterial killing assay, bacterial abundance, and membrane viability were evaluated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 44 publications
1
37
0
Order By: Relevance
“…Usually, biofilms make bacteria more resistant to antibiotics than their planktonic cells. Several other studies have shown that extractions or infusions from medicinal plants inhibit the biofilm formation in different bacteria, including S. pyogenes [41,48,49]. Our findings suggest that these HWIs of licorice roots, barberry roots, oregano, and thyme flowering shoots could be used against drug resistant- S. pyogenes .…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Usually, biofilms make bacteria more resistant to antibiotics than their planktonic cells. Several other studies have shown that extractions or infusions from medicinal plants inhibit the biofilm formation in different bacteria, including S. pyogenes [41,48,49]. Our findings suggest that these HWIs of licorice roots, barberry roots, oregano, and thyme flowering shoots could be used against drug resistant- S. pyogenes .…”
Section: Discussionmentioning
confidence: 51%
“…Spices and herbs (flavor foods) comprise a large number of phytochemicals [39], which have been revealed to possess antimicrobial properties. For example, anti- S. pyogenes ability of phenolic compounds [40,41], flavonoids [35], alkaloids [42], terpenoids [43], and tannins [35] have been reported. Qualitative UPLC analysis in the present study for HWI revealed the presence of polyphenols, flavonoids, alkaloids, terpenoids, steroids, and tannins.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial resistance in their free-living forms is a main concern for the health system, however, when they are present in biofilm, the problem is even aggravated [42]. National institutes of health announced that more than 75% of microbial infections that occur in the human body are corroborated by the development and firmness of biofilms.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is very promising in searching for a broad-spectrum antimicrobial agent with potent effect on established biofilm that may be used alone or in combination with antibiotics as this compound can interfere with the biofilm matrix allowing the antibiotic to reach the bacterial cells. In that context, Lemos et al, reported the synergistic effect between psychorubrin isolated from Mitracarpus frigidus and chloramphenicol in inhibition of biofilm of S. aureus and Streptococcus pyogenes [42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation